Peran Camat dalam menerapkan kedisiplinan aparat di Kantor Camat Taluditi Kabupaten Pohuwato - Rusni Djafar; Umar Sune (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
This study aims to examine the implementation of work discipline of civil servants at the Taluditi Sub-district Office, Pohuwato Regency, through a qualitative descriptive approach. The main focus of the study is on three forms of work discipline as stated by Mangkunegara, namely preventive, corrective, and progressive discipline. Data were collected through observation, in-depth interviews, and documentation of 10 key informants, including sub-district heads, sub-district secretaries, section heads, and staff. The results of the study indicate that the implementation of work discipline has been going quite well, marked by the firmness of the leadership, compliance with working hours, and efforts to increase employee awareness. Preventive discipline is realized through the implementation of rules and routine socialization, corrective discipline through reprimands and sanctions, and progressive discipline through the threat of heavier penalties for repeated violations. Although there have been no serious violations, employee internal motivation is the main factor in the success of discipline. This study recommends the need for special training, a reward system, and strengthening internal regulations in order to build a professional and sustainable work culture.